Effects of Dietary Total Calcium to Total Phosphorus Ratio on Growth Performance, Carcass Characteristics, Bone Mineralization, and Economics in 58- to 281-lb Pigs - C. M. Vier; S. S. Dritz; M. D. Tokach; M. A. Gonçalves; U. A. Orlando; J. R. Bergstrom; J. C. Woodworth; R. D. Goodband; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 1,134 barrows and gilts (PIC; 359 × Camborough) with an initial pen average body weight (BW) of 58.0 ± 1.57 lb were used in a 110-d growth trial to determine the effects of feeding different analyzed total calcium to phosphorus (Ca:P) ratios on performance of growing-finishing pigs from 58 to 281 lb. Pens of pigs were randomly assigned to 1 of 6 dietary treatments in a randomized complete block design with BW as a blocking factor. There were 7 replicate pens per treatment and 27 pigs per pen. The experimental diets were corn-soybean meal-based, and were fed in 4 phases. The 6 dietary treatments were formulated to contain 0:75:1, 1.00:1, 1.25:1, 1.50:1, 1.75:1, and 2.00:1 analyzed total Ca:P ratio. All diets were formulated to contain adequate standardized total tract digestiblePacross the dietary treatments in all phases. The treatments were achieved by increasing the amount of calcium carbonate at the expense of corn while maintaining monocalcium phosphate constant. Overall, increasing analyzed total Ca:P ratio increased (quadratic,P<0.05) average daily gain (ADG), average daily feed intake (ADFI), and final BW. The greatest increase was observed as the ratio increased from 0.75:1 to 1.25:1, and decreased with higher ratios. Feed efficiency was relatively similar across analyzed total Ca:P ratios of 0.75:1 to 1.75:1, and worsened (quadratic,P<0.05) at the highest ratio of 2.00:1. For carcass characteristics, hot carcass weight (HCW) and carcass ADG increased (quadratic,P<0.05) as the analyzed total Ca:P ratio increased up to 1.25:1 and started to decrease thereafter. Carcass yield decreased (quadratic,P<0.05) with increasing analyzed total Ca:P ratio. Bone mineralization increased quadratically (P<0.05) with increasing analyzed total Ca:P ratio. The greatest improvement in bone ash was observed as the ratio increased from 0.75:1 to 1.25:1, with little increase thereafter. Feed cost per pig increased quadratically (P<0.05) and feed cost per pound of gain increased linearly (P<0.05) with increasing analyzed total Ca:P ratio, with the highest feed cost and cost per pound of gain observed at 2.00:1. Gain value and income over feed cost (IOFC) increased quadratically (P<0.05), with the greatest revenue observed for pigs fed diets with 1.25:1 analyzed total Ca:P ratio, and IOFC for pigs fed 1.00:1 analyzed total Ca:P ratio. For ADG, ADFI, feed efficiency (modeled as gain-to-feed ratio, G:F), and bone ash the quadratic polynomial model demonstrated the best fit. The maximum responses in ADG, ADFI, G:F, HCW, IOFC, and bone ash were estimated at 1.38:1, 1.49:1, 1.29:1, 1.25:1, 1.10:1, and 1.93:1 analyzed total Ca:P ratio, respectively. In conclusion, for growing-finishing pigs from 53 to 287 lb, the total analyzed Ca:P ratio ranged from 1.10:1 to 1.49:1 to maximize growth performance, HCW, and IOFC criteria. A higher analyzed total Ca:P ratio, estimated at 1.93:1, was required to maximize bone mineralization.
Keywords: calcium; phosphorus; finishing pigs; growth performance; bone ash